Private Hospital Obstacles are Linked to Law No. 17 Of 2023 Concerning Health. in the Third Part Concerning the Hospital - Deni Wijaya; Abdul Kholib; Handoyo Prasetyo (PT Publikasiku Academic Solution, 2023)
Public institutions that focus on organizing and providing patient services to the community are hospitals. Private hospitals are health service bodies managed by foundations or certain groups of organizations together with educational institutions. The aim of this research is to find out what kind of constraints or barriers are experienced by private hospitals, especially those which are then linked to Law no. 17 of 2023 concerning health. This research method uses a qualitative phenomenological method aimed at describing or explaining a person's personal experiences, including experiences of relationships with other people, using literature study as a data collection procedure. The results of this research are that private hospitals in Indonesia are still not optimal in their efforts to fulfill the general provisions regarding hospitals that have been stipulated in Law no. 17 of 2023 concerning health. Due to the obstacles faced in its operations, such as the Bunda Lhokseumawe Hospital which is hampered by the lack of specialist doctors at the hospital which results in less than optimal treatment services at the hospital, then the Surya Husadha Nusa Dua Hospital which is located in Bandung, with problems. delays in the distribution of food preferences, as well as three private hospitals in Yogyakarta which were hampered by lack of medicine stock in these hospitals